INTEGRATION OF THE USER SATISFACTION MODEL METHOD IN MEASURING WEBSITE QUALITY - Khairul Fikri (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2026)
As digital presence becomes mandatory for educational institutions, ensuring website quality through systematic measurement is vital. This study investigates the Website of the Faculty of Science and Technology (FSAINTEK) at UIN Datokarama Palu, which had not undergone any formal quality assessment since its active management began in 2025. The research objective is to evaluate user satisfaction and identify critical improvement areas using an integrated measurement framework. This research proposes the integration of variables from three established models: User Satisfaction, End-User Computing Satisfaction (EUCS), and Webqual 4.0, covering Ease of Use, Customization, Download Delay, Content, and Service Interaction Quality. Utilizing a descriptive quantitative method with 53 diverse respondents, the data underwent validity, reliability, and score interpretation analysis. The findings reveal a global satisfaction index of 79.53%, classified as